Web-based Programming for Low-cost Gaming Handhelds - Moskal, Michal; Halleux, Jonathan "Peli" de; Ball, Thomas; Chatra, Abhijith; Devine, James; Hodges, Steve; Kao, Shannon; Knoll, Richard; Nickel, Galen; Russell, Jacqueline; Wunderlich, Joey; Zuniga, Daryl (Foundations of Digital Games, 2021)
Low-cost microcontroller boards like the BBC micro:bit are used to engage and inspire students worldwide to learn more about computing. Easy-to-use web-based programming environments and low-cost hardware allow novices to build physical computing systems with the micro:bit – systems that sense and respond to the real world. However, devices such as the micro:bit may not capture the attention of every student, as the interests of some may lie in graphic design, animation, or other areas that are not the main focus of physical computing. Video game creation offers the opportunity for students to engage with computing concepts from a different angle, while keeping open the possibilities for physical computing. To date however, there is no game creation platform that has both the same low-barrier to entry and low-cost hardware as the BBC micro:bit. We present MakeCode Arcade, a web app for creating video games for gaming handhelds, built on the same technologies as the BBC micro:bit, extended to support multiple microcontrollers and including a 2D game engine and easy-to-use sprite and music editors. We also designed a simple hardware specification that resulted in five different companies creating seven Arcade-compatible handhelds. Qualitative and quantitative evaluation demonstrates that Arcade enables a modern and fully web-based programming experience for low-cost microcontroller-based gaming handhelds.